The impact of peer ability and heterogeneity on student achievement: Evidence from a natural experiment - David Kiss (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2011)
This paper estimates the impact of peer achievement and variance on math achievement growth. It exploits exogenous variation in peer characteristics generated at the transition to upper-secondary school in a sample of Berlin fifth graders. Parents and schools are barely able to condition their decisions on peer characteristics since classes are newly built up from a large pool of elementary school pupils. I find positive peer effects on achievement growth and no effects for peer variance. Lower-achieving pupils benefit more from abler peers. Results from simulations suggest that pupils are slightly better off in comprehensive than in ability-tracked school systems.
Keywords: I21; I28; 330; peer effects in secondary school; comparison between ability-tracked and comprehensive school; natural experiment; Soziale Gruppe; Bildungsniveau; Bildungsabschluss; Test